2023
DOI: 10.3390/nu15040930
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Sodium Butyrate by Restoring Gut Microbiota and Inhibiting TLR4 Signaling in Mice with MPTP-Induced Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is a prevalent type of neurodegenerative disease. There is mounting evidence that the gut microbiota is involved in the pathogenesis of PD. Sodium butyrate (NaB) can regulate gut microbiota and improve brain functioning in neurological disorders. Hence, we examined whether the neuroprotective function of NaB on PD was mediated by the modulation of gut microbial dysbiosis and revealed its possible mechanisms. Mice were administered 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 73 publications
(82 reference statements)
1
32
0
Order By: Relevance
“…Therefore, in the current study, we treated BV2 cells with MPP + to induce PD‐like conditions in vitro. NaB has exhibited antiapoptotic properties in neurodegenerative disorders and can cause α‐syn degradation, inhibit overactivation of glial cells and inflammatory responses and ameliorate motor deficits in PD models 44–47 . In this study, we have explored the underlying mechanisms by which NaB exerts protective effects against PD‐like conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in the current study, we treated BV2 cells with MPP + to induce PD‐like conditions in vitro. NaB has exhibited antiapoptotic properties in neurodegenerative disorders and can cause α‐syn degradation, inhibit overactivation of glial cells and inflammatory responses and ameliorate motor deficits in PD models 44–47 . In this study, we have explored the underlying mechanisms by which NaB exerts protective effects against PD‐like conditions.…”
Section: Discussionmentioning
confidence: 99%
“…NaB has exhibited antiapoptotic properties in neurodegenerative disorders and can cause α-syn degradation, inhibit overactivation of glial cells and inflammatory responses and ameliorate motor deficits in PD models. [44][45][46][47] In this study, we have explored the underlying mechanisms by which NaB exerts protective effects against PD-like conditions. NaB treatment inhibits the microglia-mediated neuroinflammation by activating the K ATP channels as indicated by following findings: After treatment with 100 μM MPP + , the morphology of BV2 wells changed from resting state to activated state.…”
Section: Nab Prevents the Production Of No And Pro-inflammatory Cytok...mentioning
confidence: 99%
“…For example, recent studies have shown that the gut microbiota is essential in the onset and maintenance of diseases that are related to the CNS, such as mood disorders, schizophrenia, or autism, and even with neurodegenerative disorders such as Alzheimer's disease (AD), Parkinson's disease (PD), multiple sclerosis (MS), amyotrophic lateral sclerosis (ALS), or Huntington s disease, among others [55][56][57]. In addition, we now know that the certain markers of the pathology are related to an increase in intestinal permeability, called leaky gut syndrome [58].…”
Section: Dysbiosis In Neurodegenerative Pathologiesmentioning
confidence: 99%
“…On the other hand, it is known that the determining marker of the pathology is the presence of Lewy bodies that develop in the ENS, and this is associated with an increase in intestinal permeability [58]. Leaky gut syndrome encourages damage to this tissue to promote the inclusion of harmful substances, and is associated with the presence of dysbiosis, which would alter intestinal permeability and thus promote the occurrence of the pro-inflammatory response [177,178].…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…It has been reported that microbiota-derived short-chain fatty acid (SCFA) butyrate enhances oxidative metabolism and uncouples Krebs cycle from glycolytic flux in immune cells (Bachem et al, 2019). Butyrate had a neuroprotective impact on mouse models of Parkinson’s disease, likely due to the downstream regulation of gut microbiota and inhibition of gut-brain axis inflammation (Guo et al, 2023). Butyrate reduces neuroinflammation and microglia activation in several experimental models of disease (Caetano-Silva et al, 2023; Huuskonen et al, 2004; Wenzel et al, 2020).…”
Section: Introductionmentioning
confidence: 99%